Sustainability and interdisciplinarity: innovations and challenges for postgraduate programmes on the Environment and Society. The case of the Centre for Sustainable Development at the University of Brasilia - do Nascimento, Elimar Pinheiro; Amazonas, Mauricio; Vilhena, Andréa (Revista Brasileira de Pós-Graduação, 2014)
Held by the UN in 1992, the Conference on Environment and Development reinforced the concept of Sustainable Development, which was originated in the preceding decade. Three years later the Centre for Sustainable Development was established at the Universidade de Brasilia (CDS/UnB), which has witnessed a boom in interdisciplinary postgraduate programmes as part of a growing trend among other academic unitsdealing with the relationship between the environment and society. This article reflects on some of the innovations and challenges faced by the CDS, which proclaims its identity built on the binomial “sustainability and interdisciplinarity”. It therefore addresses both notions before discussing the specific path of the Centre with respect to its innovative components and challenges. As concluding remarks, the article presents thoughts on the new design of the field of sustainability and on the challenges for postgraduate programmes that deal with this matter.